THE POTENTIAL USE OF Ca(NO3)2 TO IMPROVE SALINITY TOLERANCE IN DATE PALM (Phoenix dactylifera L.) - Alturki, Saleh M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The study was conducted to investigate the impact of Ca(NO3)2 on different levels of salt-stress in date palm. Three-years-old date palm plants were subjected to four NaCl levels: 50, 100, 150 and 200 mM. The saline solutions were supplemented with 0, 5, 10 and 20 mM Ca(NO3)2. The combined NaCl/Ca(NO3)2 treatments were conducted over a period of 10 weeks. Control plants were only subjected to the four salinity levels with no Ca (NO3)2 addition. Results showed an inhibitory effect of salinity on almost all plants’ parameters under investigation, mainly the accumulation of ions such as N, K, Ca, plant dry weight, chlorophyll and net photosynthesis rate. Addition of Ca (NO3)2 in the solution was more beneficial when added in a moderate concentration (10 mM) compared to lower (5 mM) and higher (20 mM) under all salinity levels. The addition of 10 mM Ca (NO3)2 noticeably enhanced chlorophyll content under 50 mM Na Cl (2.5 mg/100 cm2) and 150 mM NaCl (2 mg/100 cm2). In addition, 10 mM Ca (NO3)2 reduced the accumulation of Na and Cl in plant parts. For instance, in trees subjected to 10 mM Ca (NO3)2, Cl content in leaves and stems under 50 mM Na Cl were 0.23% and 0.65%, respectively. On the other hand, Cl content under 100 mM Na Cl and 200 mM Na Cl were lower compared to their corresponding control treatments. It seems that the use of Ca (NO3)2 had ameliorative effects on salt-stressed date palm plants when used with moderate concentrations.